Nature's "every day disabille": John Clare, shattered vision, and the everyday poetics of noon - Effinger, Elizabeth (Romanticism on the Net)

(untitled) (Université de Montréal, 2019)
This article examines the phenomenon of noon in John Clare's poetry. Drawing heavily on Deleuze's notion of the middle or the intermezzo, this article makes the case that Clare's noon or midday is an exploration of what Deleuze calls life's "meantimes (des entre-temps), between-moments," and one that importantly offers us a view into the experience of the intermezzo. For Clare, noon affords a new mode of perception, one that he repeatedly frames as a shattered vision: at noon "it seems / As if crooked bits of glass / Seem'd repeatedley to pass" (6-8). While also considering the appearance of noon in the work of Clare's contemporaries, such as Shelley and Constable, the uniquely shattered vision that accompanies Clare's experience of this seemingly ubiquitous spacetime is a way to see the world in a different way outside of our routinized or habitualized modes of everyday perception. Furthermore, against a dominant tradition that imagines thought as taking flight at dusk (following Hegel), Clare's turn to noon offers thought a different line of flight. For Clare, midday becomes an important moment of knowledge, a defamiliarized moment of shattered perception, a creative synthetic event of sympoeisis, that is, the practice of mixing and making together.